2022
DOI: 10.1111/arcm.12747
|View full text |Cite
|
Sign up to set email alerts
|

There’s more to a vessel than meets the eye: Organic residue analysis of ‘wine’ containers from shipwrecks and settlements of ancient Cyprus (4th–1st century bce)

Abstract: Despite growing evidence to the contrary, wine remains the assumed content of many types of ancient pottery. Vessels from the Kyrenia and Mazotos shipwrecks, and Yeronisos island presumed to have contained wine were subjected to three different extraction protocols to test the assumption that these vessels were used to import and serve wine. Chemical extracts reveal grapevine products but also other fruit juice, beeswax and plant oil, sometimes mixed with grapevine products due to intentional mixing or reuse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The results show that sample 175, a Spanish olive jar, contains levels of tartaric acid that indicate a past content of wine. This result is consistent with the suite of diterpenoids also found in this samples, as many wine vessels were lined with conifer products in the past in order to more effectively seal the permeable sides of the vessel and contribute antimicrobial properties to the wine (Briggs et al 2022 ; Drieu et al 2021 ; Heron and Pollard 1988 ; Pecci et al 2017 , 2013 ; Pollard and Heron 1996 ). Tamarind products can also impart a similar ratio of tartaric acid to malic acid in ceramic vessels (Drieu et al 2021 , p. 5); however, tamarind was not present in this region during this time period, having been transported to Mexico and Central America for the first time later in the sixteenth century by Spanish and Portuguese colonists from tropical regions of Africa (Tamale et al 1995 ).…”
Section: Resultssupporting
confidence: 87%
“…The results show that sample 175, a Spanish olive jar, contains levels of tartaric acid that indicate a past content of wine. This result is consistent with the suite of diterpenoids also found in this samples, as many wine vessels were lined with conifer products in the past in order to more effectively seal the permeable sides of the vessel and contribute antimicrobial properties to the wine (Briggs et al 2022 ; Drieu et al 2021 ; Heron and Pollard 1988 ; Pecci et al 2017 , 2013 ; Pollard and Heron 1996 ). Tamarind products can also impart a similar ratio of tartaric acid to malic acid in ceramic vessels (Drieu et al 2021 , p. 5); however, tamarind was not present in this region during this time period, having been transported to Mexico and Central America for the first time later in the sixteenth century by Spanish and Portuguese colonists from tropical regions of Africa (Tamale et al 1995 ).…”
Section: Resultssupporting
confidence: 87%
“…In C 6 –C 24 saturated fatty acids, as well as unsaturated FFAs, such as oleic (C 18:1ω9 , cis -9-octadecenoic acid) and linoleic acid (C 18:2ω6 , cis -9, cis -12-octadecadienoic acid) acids, a variable composition of C 14 –C 20 alcohols, C 16 and C 18 MAGs, and C 23 –C 29 n -alkanes was detected, together with small organic acids and monosaccharides deriving from glucose and glycerol, in pottery jars, vessels and amphorae possibly employed to store, contain and transport, at the same time or in different moments, vegetable oils or animal products with fermented alcoholic beverages (grape juice, wine) or sauces (Roman sapuum, mulsum or defrutum) [ 44 , 45 , 46 ]. Although tartaric and syringic acids were traditionally considered as wine biomarkers, the identification of wine in archaeological pottery remains controversial, since the aforementioned compounds can come from different sources [ 45 , 47 , 48 , 49 ]. Glutaric, fumaric, lactic malic, succinic and malonic acids, together with proper archaeological and historical support, could provide a more reliable interpretation of the data [ 46 ].…”
Section: Lipids and Archaeological Biomarkersmentioning
confidence: 99%
“…Nearly all the amphorae are of Chian type, with long, straight necks and sharp-edged shoulders, but a few others have also been recovered, including North Aegean types and Mushroom-rim/ Solokha I forms from the south-eastern Aegean (Demesticha 2011: 41–46) (Figures S1–S2 in the online supplementary material (OSM)). The majority probably carried wine (Briggs et al 2022), but considerable quantities of olive pits were found inside six amphorae (out of more than 250 minimum number of individual (MNI) cargo amphorae that were recovered), ranging between 58 and 2712 pits per amphora. The small number of amphorae containing olives suggests that these were provisions for the crew rather than a cargo (Demesticha 2011: 48; Briggs et al .…”
Section: The Mazotos Shipwreckmentioning
confidence: 99%
“…The small number of amphorae containing olives suggests that these were provisions for the crew rather than a cargo (Demesticha 2011: 48; Briggs et al . 2022). Excavation has also revealed part of the hull and planking, as well as the remains of three anchors.…”
Section: The Mazotos Shipwreckmentioning
confidence: 99%
See 1 more Smart Citation